2019
DOI: 10.1177/2150132719895188
|View full text |Cite
|
Sign up to set email alerts
|

Use of SGLT-2 Inhibitors in Patients With Type 1 Diabetes Mellitus

Abstract: Introduction: Sodium-glucose cotransporter 2 (SGLT-2) inhibitors are the newest class of oral antihyperglycemic medications approved for the treatment of type 2 diabetes mellitus (DM2). Although they are not approved for use in type 1 diabetes mellitus (DM1), SGLT2 inhibitors may help DM1 patients achieve their HbA1c goals by decreasing their insulin requirements, without inducing hypoglycemic episodes and weight gain. Methods: We conducted a retrospective chart review of 26 patients with DM1 treated with off-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Consequently, the data about the off-label use of medicines are scarce, as it is often associated with a practice with no legal framework [69]. The off-label use of ADs is not well documented, but some studies suggested the use of NADs for T1DM [70][71][72][73][74][75], obesity [70,76], polycystic ovarian syndrome [77][78][79], dermatological diseases [80,81], and as a senolytic [82][83][84]. Recently, the European Medicines Agency approved the SGLT inhibitors dapagliflozin and sotagliflozin as adjuvant treatments to insulin for T1DM in adults [85], and insulins were already recommended in T2DM in the previous guidelines.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Consequently, the data about the off-label use of medicines are scarce, as it is often associated with a practice with no legal framework [69]. The off-label use of ADs is not well documented, but some studies suggested the use of NADs for T1DM [70][71][72][73][74][75], obesity [70,76], polycystic ovarian syndrome [77][78][79], dermatological diseases [80,81], and as a senolytic [82][83][84]. Recently, the European Medicines Agency approved the SGLT inhibitors dapagliflozin and sotagliflozin as adjuvant treatments to insulin for T1DM in adults [85], and insulins were already recommended in T2DM in the previous guidelines.…”
Section: Strengths and Limitationsmentioning
confidence: 99%